Long Non-coding RNA Maternally Expressed 3 Increases the Expression of Neuron-Specific Genes by Targeting miR-128-3p in All-Trans Retinoic Acid-Induced Neurogenic Differentiation From Amniotic Epithelial Cells - Gao, Yuhua; Zhang, Ranxi; Wei, Guanghe; Dai, Shanshan; Zhang, Xue; Yang, Wancai; Li, Xiangchen; Bai, Chunyu (Frontiers in Cell and Developmental Biology, 2019)
MiR-128-3p is a brain enriched microRNA that participates in the regulation of neural cell differentiation and in the protection of neurons, but the mechanisms by which miR-128-3p regulates its target and downstream genes to influence cell fate from adult stem cells are poorly understood. In this study, we show down-regulation of miR-128-3p during all-trans retinoic acid (ATRA) induced neurogenic differentiation from human amniotic epithelial cells (AECs). We investigated miR-128-3p in both the Notch pathway and in the expression of neuron specific genes predicted to be involved in miR-128-3p signaling to elucidate its role in the genetic regulation of downstream neurogenic differentiation. Our results demonstrate that miR-128-3p is a negative regulator for the transcription of the neuron specific genes, β III-tubulin, neuron specific enolase (NSE), and polysialic acid-neural cell adhesion molecule (PSA-NCAM), via targeting Jagged 1 (JAG1) to inhibit the activation of the Notch signaling pathway. We also use bioinformatics algorithms to screen for miR-128-3p interactions with long non-coding RNA (lncRNA) and circular RNA (circRNA) as competing endogenous RNAs, to further elucidate underlying down-regulated molecular mechanisms. The lncRNA maternally expressed 3 (MEG3) is up-regulated by the ATRA/cAMP/CREB pathway, and it, in turn, is directly down-regulated by miR-128-3p to increase the amount of neuron differentiation. Endogenous miRNAs are, therefore, involved in neurogenic differentiation from AECs and should be considered during the development of effective cell transplant therapies for the treatment of neurodegenerative disease.